RP-HPLC Method for the Estimation of Capecitabine in Tablet Dosage Forms - Srinivasu, K.; Venkateswara Rao, J.; Appala Raju, N.; Mukkanti, K. (Asian Journal of Chemistry, 2010)
A simple, accurate, sensitive and fast reverse phase high performance liquid chromatographic method was developed for the determination of capecitabine in tablet dosage form. A symmetry C18 5 μ, 75 mm × 4.6 mm i.d., in isocratic mode, with a mixture of ammonium acetate with 0.1 % formic acid as buffer and methanol (45:55 v/v) as the mobile phase with flow rate of 1.2 mL/ min and analyte was monitored at 305 nm with run time of 5 min. The retention time of the capecitabine was achieved at 3.024 min. The detector response was linear in the concentration of 1.5-22.5 μg/mL, assay is 99.9 % and the limit of detection and limit of quantification was 0.05 and 0.19 μg/mL, respectively. The method was validated by determining its selectivity, sensitivity, precision, linearity, accuracy and LOD and LOQ. The proposed method is simple, fast, sensitive, accurate and precise and hence can be applied for routine quality control of capecitabine in tablet dosage form.